2005
DOI: 10.1016/j.molcel.2005.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Eukaryotic Ribosomal Proteins in Maturation and Transport of Pre-18S rRNA and Ribosome Function

Abstract: Despite the rising knowledge about ribosome function and structure and how ribosomal subunits assemble in vitro in bacteria, the in vivo role of many ribosomal proteins remains obscure both in pro- and eukaryotes. Our systematic analysis of yeast ribosomal proteins (r-proteins) of the small subunit revealed that most eukaryotic r-proteins fulfill different roles in ribosome biogenesis, making them indispensable for growth. Different r-proteins control distinct steps of nuclear and cytoplasmic pre-18S rRNA proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
323
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(348 citation statements)
references
References 53 publications
(56 reference statements)
21
323
2
1
Order By: Relevance
“…It has become increasingly apparent that the hierarchical assembly of small ribosomal subunit domains is largely conserved from bacteria to eukaryotes (Held et al 1974;Ferreira-Cerca et al 2005Mulder et al 2010;O'Donohue et al 2010;Chen and Williamson 2013;Clatterbuck Soper et al 2013). What remained unclear is whether the same is true for large ribosomal subunits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has become increasingly apparent that the hierarchical assembly of small ribosomal subunit domains is largely conserved from bacteria to eukaryotes (Held et al 1974;Ferreira-Cerca et al 2005Mulder et al 2010;O'Donohue et al 2010;Chen and Williamson 2013;Clatterbuck Soper et al 2013). What remained unclear is whether the same is true for large ribosomal subunits.…”
Section: Discussionmentioning
confidence: 99%
“…RP depletions in yeast and siRNA-mediated knockdowns in cultured mammalian cells showed that most RPs are essential for ribosome biogenesis (Ferreira-Cerca et al 2005;Robledo et al 2008;Poll et al 2009;Babiano and de la Cruz 2010;O'Donohue et al 2010;Jakovljevic et al 2012;Gamalinda et al 2013). However, phenotypic analyses of these mutants were primarily limited to assaying effects on pre-rRNA processing and nucleocytoplasmic export of preribosomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Un système de contrôle de cette maturation est assuré en partie par l'assemblage de protéines ribosomiques. Ainsi, la petite sous-unité n'est exportée du noyau que lorsque les protéines RPS15/RPS18 (selon la nouvelle nomenclature, uS19/uS13, [21]) et RPS5/RPS28 (eS25/eS28) sont assemblées sur la particule [22,23].…”
Section: Export Des Pré-ribosomesunclassified
“…The small subunit protein RPS14, the yeast homolog of the bacterial S11 protein, directly binds helix 23 of 18S rRNA (Fewell and Woolford Jr., 1999;Mayolo and Woolford Jr., 2003). Recently, it was reported that RPS14 is an essential protein necessary for the maturation of the 40S ribosomal subunit (Larkin et al, 1987;Moritz et al, 1990;Paulovich et al, 1993;Ford et al, 1999;Jakovljevic et al, 2004) and the processing of 18S pre-rRNA (Ferreira-Cerca et al, 2005;Ebert et al, 2008). And in the 40S subunit, RPS14 helps to form the mRNA exit channel along with its interacting protein RPS5 (Yusupov et al, 2001).…”
Section: Introductionmentioning
confidence: 99%